2005
DOI: 10.1097/01.aog.0000174580.24281.e6
|View full text |Cite|
|
Sign up to set email alerts
|

Underreporting of Pregnancy-Related Mortality in the United States and Europe

Abstract: This study shows the limitations of maternal mortality statistics based on International Classification of Diseases cause-of-death codes alone. Linkage of births and deaths registers should routinely be used in the ascertainment of pregnancy-related deaths. In addition, extension of the definition of a maternal death should be considered. Beyond pregnancy-related mortality ratios, considering the specific distribution of causes-of-death is important to define prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 22 publications
0
106
1
10
Order By: Relevance
“…Classification by cause of death in vital statistics, however, can be imprecise for rare causes of deaths in the industrialised countries. 20,21 Inversely, the data on which our study is based come from recent detailed national studies: the information about the controls is detailed on the characteristics of the women, the pregnancy and the delivery. For the cases, the information is very specific about management (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Classification by cause of death in vital statistics, however, can be imprecise for rare causes of deaths in the industrialised countries. 20,21 Inversely, the data on which our study is based come from recent detailed national studies: the information about the controls is detailed on the characteristics of the women, the pregnancy and the delivery. For the cases, the information is very specific about management (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to most developed countries and their cities, São Paulo City has a much higher MMR 8 with an underreporting rate of 52.2%, which is within the range observed in Europe and in the United States. 9 Hypertensive disorders in pregnancy, delivery, and puerperium represented the main cause of maternal death in São Paulo City, resulting in 23.3% of deaths. In contrast, arterial hypertension occupies third place (15.9%) after thromboembolism (19.9%) and hemorrhage (18.2%) in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent report of the CEMD (for 2006-2008) identified 60% more maternal deaths than were reported in the routine civil registration system (12). Other studies on the accuracy of the number of maternal deaths reported in civil registration systems have shown that the true number of maternal deaths could be twice as high as indicated by routine reports, or even more (13,14). Appendix 1 summarizes the results of a literature review for such studies where misclassification on coding in civil registration could be identified.…”
Section: Approaches For Measuring Maternal Mortalitymentioning
confidence: 99%
“…Maternal mortality data available from countries varied in terms of the source and type, and countries were classified accordingly into three groups (Table 1, and Appendices 2-4). In total, the database of observed MMR and PM includes 3200 countryyears of data, of which 2125 country-years are derived from vital registration data, 895 from survey-based sisterhood data, and the remainder from surveillance systems (87), other household surveys (31), censuses (19), RAMOS (16), sample registration systems (14) and other sources (13). Observation intervals refer to 1985 or later.…”
Section: Sources Of Country Data Used For the 1990-2010 Estimatesmentioning
confidence: 99%